Pelatihan Mengenalkan Diastasis Rektus Abdominis pada Tenaga Kesehatan di Desa Talang Jawa UPTD Puskesmas Tanjung Agung - Suparno Suparno; Meilina Estiani; Aisyah Aisyah (Indonesia Berdaya, 2022)
Physiologically in pregnant women there will be changes in the abdominal wall, in which the abdominal wall muscles will stretch/an increase in abdominal distension as a result of increasing uterine volume which has an impact on decreasing abdominal muscle tone. The abdominal wall muscles stretch and eventually lose some muscle tone. During the third trimester, the rectus abdominis can separate, causing the abdominal contents to protrude toward the midline of the body, this separation is known as diastasis recti abdominis. Based on the author's survey of 10 midwives in obtained, the level of knowledge of the midwives about diastasis rectus Abdominis  (DRA), sufficient level of knowledge was 40% and less than 60%, of the midwife was didn,t know how to conduct a DRA examination on postpartum mothers. The purpose of this activity is to increase the knowledge and skills of participants how to do check  DRA And evaluate  result of competence of the midwife in providing services to postpartum women in their clinic already applies Diastasis Recti Abdominis examination to every patient. Conclusion: There was an increase of knowledge participants before and after training. There was an increase in the ability of participants to perform an examination of Diastasis Rectus Abdominis on postpartum mothers, both before and after the training